Association between exclusive breastfeeding history and diarrhea among children under five: - - Audry Rizki Hasanah; Niputu Sudiadnyani; Rakhmi Rafie; Yesi Nurmalasari (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Toddlers are a vulnerable age group to diarrhea due to their immature immune system and digestive tract function. Diarrhea remains a major health problem with a high incidence among toddlers, both globally and nationally. One of the preventive efforts against diarrhea is exclusive breastfeeding, as breast milk contains nutrients and immunological components that protect the infant’s digestive tract from infection. Purpose: To examine the association between a history of exclusive breastfeeding and diarrhea among children under five. Method: This study employed an analytical cross-sectional design. The study was conducted at the Kemiling Inpatient Community Health Center in Bandar Lampung City. The population in this study was 112 mothers with toddlers, with a sample size of 53 respondents using consecutive sampling technique. Data analysis used the Chi-Square test and Odds Ratio (OR) test. Results: The results showed that 30 respondents (56.6%) provided exclusive breastfeeding and 23 respondents (43.4%) did not provide exclusive breastfeeding. Toddlers who experienced diarrhea were 23 respondents (43.4%). The results of the Chi-Square test analysis obtained a p-value = 0.001 (p < 0.05) with an Odds Ratio (OR) value of 0.088 (95% CI: 0.024–0.321), which indicates a significant relationship between the history of exclusive breastfeeding and the incidence of diarrhea in toddlers. Toddlers who receive exclusive breastfeeding have a lower risk of experiencing diarrhea than toddlers who do not receive exclusive breastfeeding. Conclusion: There is a significant relationship between a history of exclusive breastfeeding and the incidence of diarrhea in toddlers. Exclusive breastfeeding is protective against diarrhea in toddlers.